×-2 y+3
⁻⁻⁻⁻ - ⁻⁻⁻⁻⁻ =x+2y
2 5


3-2x 4y-2
₋₋₋₋ - ₋₋₋₋₋₋=2 - x
3 6 ⁻⁻⁻⁻
2
i to ma byc w dużej klamże { }



Odpowiedź :

Eddiss
×-2 y+3
⁻⁻⁻⁻ - ⁻⁻⁻⁻⁻ =x+2y /*10
2 5


3-2x 4y-2
₋₋₋₋ - ₋₋₋₋₋₋=2 - x /*6
3 6 ⁻⁻⁻⁻
2



(5×-2)-2( y+3)=10(x+2y)
2(3-2x)-( 4y-2)=3(2-x)

5×-2- 2y-6=10x+20y
6-4x-4y+2=6-3x


5×-10x=20y+2y+8
-4x-4y=6-3x-8

-5×=22y+8 /*(-1)
-4x-4y=6-3x-8


5×=-22y-8
-x-4y=-2

×=-4,4y-1,6
-(-4,4y-1,6)-4y=-2

×=-4,4y-1,6
4,4y+1,6-4y=-2

×=-4,4y-1,6
0,4y=-3,6

×=-4,4y-1,6
y=-9

×=-4,4*(-9)-1,6
y=-9


×=38
y=-9